FORMATION OF ECONOMIC BEHAVIOR OF ENTERPRISES: PROCESS AND FEATURES - SKAKOVSKYI, Viacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The work considers the process of forming of economic behavior of enterprises on the basis of features of functioning of modern enterprises. It was determined that the process of forming an enterprise's economic behavior strategy is characterized by a set of features: the level of development, regularity, uncertainty, the number of possible alternative solutions, which should be taken into account when forming economic behavior; information used in the formation of economic behavior; time horizons; interdependence; detail; assessment accuracy; degree of risk.Also the necessity of opening of forming of economic behavior of enterprises through the prism of intercommunication with strategy and strategy of behavior of enterprises is grounded. It was determined that the strategic level of the enterprise's economic behavior directs its actions and activities, the tactical level - directs, the situational level - corrects (coordinates) when unforeseen factors are detected. The determined levels of behavior indicate that the economic behavior of enterprises covers a wider conceptual substance, in which the strategic level is only a separate component.The process of forming of economic behavior of enterprises is improved from position of generalization of three levels of activity: strategic, tactical and situation. It was established that the process of formation of economic behavior of the enterprise has a cyclical nature. The initial information entering the enterprise strategy formation system goes through the stages of information processing and analysis, after which determining factors are identified and their optimal coordination with other factors is ensured. The next stage is the formation of a strategic goal, matching the goals of the strategy with the real potential of the enterprise and determining and evaluating alternative strategies: limited growth, expansion, reduction (liquidation, cutting off excess, reduction and reorientation), a combination of three options. After identifying and evaluating alternative options, a specific strategy is chosen that would ensure the fulfillment of the set goals. To increase the probability of strategy implementation, a behavior strategy is developed, namely a set of actions for the implementation of a strategic goal. The formed set of actions is implemented in the real economic life of the enterprise, taking into account current and unforeseen changes that have occurred.
Keywords: economic behavior; strategy; behavioral strategy; process; levels of activity